Uso de biocarvão na recuperação de tecnossolos formados por rejeito de mineração de ferro - Souza, Wendell Rangel Queiroz de (2018)
Mining is an anthropogenic activity that has caused several environmental damage, mainly soil degradation by the deposition of tailings in the superficial layers, creating highly degraded sediments. Addition of biochar on sediments can improve their physical, chemical, and biological properties and, consequently, the vegetal cover. The main goal of this work was to evaluate the influence of biochar application on chemical properties of Technosols formed by the deposition of tailings from iron mining and its effect on the initial development of a forest specie that is used in the recovery of degraded areas. Technosol samples which were formed after the rupture of an iron ore tailing dam in the district of Bento Rodrigues -Mariana-MG, were collected. Biochars were produced from different biomasses: waste of sugar cane, wood sawdust and their mixture. Chemical and physical characterization of the biochars were performed. Different doses of each biochar (5, 10, and 15%) were mixed with the Technosol. After applications, Schinus terebinthifolius seedlings were planted, and evaluated at 70 days after the initial growth. Thereafter, Technosol samples were homogenate and analyzed. Plant height, stem diameter, fresh mass of shoot and root and the dry mass of the shoot and the root of the seedlings were evaluated. Chemical and physical properties such as gravimetric yield, volatile materials, fixed carbon, ash content, pH, electrical conductivity, specific surface area, cation exchange capacity and C, N, O and H content showed variation. All biochar application in the Tecnosols increased pH, organic matter contents, and availability of K, P, S and B. They also had decreased the potential acidity, availability of Ca, Mg, Zn, Cu and Al, cation exchange capacity, and base saturation. The improvement caused by biochar did not affect seedling initial growth due high Fe concentration in the tecnosol.